Meraih Motivasi Anak Terhadap Perawatan Gigi dengan Bahan Tambal Warna-Warni - Yetty Herdiyati Nonong; Arlette Suzy Puspa (Jurnal Material Kedokteran Gigi, 2013)
Early dental treatment on caries lesions of primary tooth is important as an attempt to maintain child’s oral health. But until recently the prevalence of dental caries among children still show a pretty high number. One reason for this is because it is still a lack of knowledge of dental health maintenance at home and also the presence of fear or anxiety towards dental treatments. Motivate a child to get the dental treatment requires efforts that can reduce the fear or increase the child’s interest in dental treatment. One of these efforts is to use a colored filling material. Children’s involvement in choosing the desired color can make dental filling as an exciting procedure without reducing the effectiveness of the treatment. This paper will discuss about the compomer as a filling material, which available in several color options.